Membangun Keunggulan Kompetitif Perguruan Tinggi Berbasis Pondok Pesantren Melalui Manajemen Pemasaran Yang Efektif - Bahrudin Yusuf (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
The main objective of this research is to understand and formulate effective marketing strategies for pesantren-based colleges, taking into account the social and cultural contexts that exist in them. This research uses a qualitative approach with a case study to analyze marketing management strategies in pesantren-based colleges. Data were collected through in-depth interviews with managers, marketing staff, and students, as well as participatory observation and documentation analysis. The data were analyzed using thematic analysis techniques to identify key themes such as branding strategy, market segmentation, student services, and utilization of technology in marketing. This research aims to provide in-depth understanding and recommendations to enhance competitive advantage through effective marketing. The conclusion of this discussion shows that boarding school-based universities have challenges and opportunities in developing marketing strategies. Differentiation based on religious values becomes a competitive advantage, offering quality education with a focus on character building and spirituality. The utilization of digital technology, such as social media and websites, increases visibility and accessibility, strengthening the modern image without abandoning religious values. However, limited resources in budget, professional personnel, and understanding of data-driven marketing are still obstacles. Internal capacity building and external collaboration are needed to optimize a more structured and data-driven marketing.